Viral Pandemics and Its Effect on General Public - A Review - S, KESAVA PRIYA; R. V, GEETHA; V, VISHNU PRIYA (The journal of contemporary issues in business and government, 2020)
The pandemic is an outbreak of disease which spreads across a particular region or regions. The key features of pandemic include wide geographic extension, disease movement, novelty, severity, high attack rates and explosiveness. It also involves minimal population immunity, infectiousness and contagiousness which helps us to understand what pandemics are and its effect on the public. Viral pathogens can transform quickly, which allows them to pass from wild animals to humans. These emerging diseases endanger human lives and have major socioeconomic impacts. The aim of the review is to know about the viral pandemics and its effect on the general public. Human behaviour and demographic factors significantly increase these risks, and the speed with which humans travel between continents can cause the runaway spread of pandemics. The literature review was carried from scopus and pubmed databases from 2000 till date. The viral pandemic disease and its effect on the general public is the outbreak of global scale. Children, older people, pregnant women and people with weakened immune systems are often affected by these pandemics. The cause, prevention and control of pandemics had been studied.